Cautionary tale of right ventricular perforation during Micra™ leadless pacemaker insertion. Issue 6 (14th November 2022) - Gulkarov, Iosif; Stein, Louis H.; Karanam, Ravindranath N.; Lackey, Adam; Dobesh, David; Ahmad, Ahsanuddin; Salemi, Arash
Abstract: Transcatheter pacing systems are self‐contained, leadless, devices that offer the potential benefits of avoiding complications related to pectoral pocket and upper extremity vascular access. These systems in preapproval trials demonstrated excellent safety profile with the incidence of device‐related cardiac perforation as low as 1.6% with Micra™ (Medtronic) and 1.3% in Nanostim (Abbott). In post‐approval registry of Micra™ TPS, the rate of major complications was even lower than in the investigational study ranging from 0.63% to 0.77%. Recently, published report found much higher rates of need for rescue surgery, shock, tamponade, and death among patients implanted with the Micra™ device when compared with transvenous devices. This case report describes two cases of major right ventricular perforation requiring surgical intervention.